Extra-anatomic “Rendezvous” Technique in Management of Biliary Complications Following Liver Surgery: A Technical Note - Wafa Boughanmi; Haytham Derbel; Yann Lebaleur; Melanie Chiaradia; Vania Tacher; Hicham Kobeiter (The Arab Journal of Interventional Radiology)
We describe extra-anatomic “rendezvous” technique for the management of bile leak associated with biliary stricture following hepatic surgery in two patients. In the procedure, the endoscopic guidewire was snared from the biloma cavity and pulled through the percutaneous access allowing for a drain to be placed. Both procedures were technically successful.